ATIM-43. PLASMA EXTRACELLULAR VESICLE MIRNA SIGNATURES IN GBM PATIENTS RECEIVING AN EXPERIMENTAL IMMUNOTHERAPY. (11th November 2019) - Cumba-Garcia, Luz; Dehankar, Mrunal; Nair, Asha; Parney, Ian
Abstract: Patients with glioblastoma (GBM) have a median survival of 15 months despite aggressive treatment. Immunotherapies such as dendritic cell (DC) vaccines have modest clinical efficacy in small clinical trials. Treatment-related pseudo-progression confounds outcome assessment by MRI, particularly in patients receiving immunotherapy. Thus, there is a need for additional non-invasive methods to monitor treatment response. Extracellular vesicles (EVs), especially plasma exosomes, contain tumor-specific microRNA (miRNA) cargo that could serve as a liquid biopsy to distinguish true progression from treatment-related pseudo-progression. Plasma exosomes were isolated by serial density gradient ultracentrifugation from 20 newly diagnosed GBM patients enrolled in a clinical trial of allogeneic tumor lysate-pulsed autologous DC vaccination. Short non-coding RNA sequencing and bioinformatics analysis was performed for each patient at three time points (TP): pre-vaccine (TP1), post-initial vaccine (TP2), and at end of treatment (TP3). miRNA expression analysis revealed a total of 14 upregulated and 12 downregulated miRNAs across time points (p-value < 0.05, |logFC| >1), few of which have been previously reported to be differentially expressed in GBM. Interestingly, patients' miRNA profile expression differed more at the beginning of treatment (e.g. TP1-vs-TP2) and at subsequent time points (e.g. TP2-vs-TP3). Ingenuity Pathway Analysis is in progress to identify pathways associated with immunotherapy treatment response in malignant gliomas. In conclusion, miRNA sequencing from GBM patients' plasma exosomes enrolled in our DC clinical trial shows marked differential miRNA expression between time points. These results suggest that as patients progress through treatment, consistent differences in plasma exosomal miRNA expression profile can be identified that could be utilized as predictors of treatment response. Thus, plasma EVs may serve as a robust platform to monitor treatment outcome.